Control of minimum film-boiling quench temperature of small spheres with micro-structured surface. (June 2018) - Jun-young, Kang; Gi Cheol, Lee; Kaviany, Massoud; Hyun Sun, Park; Moriyama, Kiyofumi; Moo Hwan, Kim
Highlights: Minimum film-boiling quench temperature is strongly influenced by surface micro-structures. Liquid–solid contact in film boiling is caused by local temperature drop of micro-structures. Local temperature drop of surface micro-structures can be explained by fin-theory. The hybrid Biot number Bih elucidates the local temperature drop, causing liquid–solid contact. T MFB increase is related to the Bih, containing the characteristics of micro-structures. Surface micro-structures with high Bih makes T MFB increase be maximized. Abstract: The control of minimum film-boiling quench temperature, T MFB is investigated in water quenching experiments with several micro-structured surfaces on small spheres (diameters 10 and 15 mm) under saturation temperature T sat and 1 atm. The results show increase in T MFB and is related to the temperature drop across the micro-structures, and affected by its effective thermal conductivity 〈 k〉, height L, and base diameter D, based on the fin theory. The local temperature drop of surface microstructure depends on the hybrid Biot number, B i h = h L 2 / ( 〈 k 〉 D ), where h is the heat transfer coefficient. The liquid–solid contact depends on this microstructure-tip temperature, and a model for T MFB with synthetic surface micro-structure is proposed and compared with the experimental results. The theoretical limit of maximum T MFB (under saturated water at 1 atm) for surface micro-structured small sphere is reached when Bih is beyond 10 2 .